2019
DOI: 10.3389/ffgc.2019.00077
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Tree Mixing and Drought on a Primary Forest Pest

Abstract: Climate change and biodiversity erosion are two major threats to the vitality of the world's forests. However, it is difficult to predict the extent to which tree diversity and environmental conditions interact to modify forest health, and in particular resistance and/or tolerance to insect pests. We used a tree diversity experiment with an irrigation treatment to investigate the effect of mixing and diluting host pines (Pinus pinaster) amongst broadleaved trees on pine stem borer (Dioryctria sylvestrella) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The impact of mixed forests on pathogens has been less extensively studied, but several papers report cases of associational resistance (Hantsch et al, 2014;Pautasso, Holdenrieder, & Stenlid, 2005). However, previous studies showed mixed forests do not always show associational resistance to pests and pathogens (Kambach, Kühn, Castagneyrol, & Bruelheide, 2016;Schuldt et al, 2010), suggesting that associational effects may be context dependent, for instance, on abiotic conditions (Jactel, Poeydebat, van Halder, & Castagneyrol, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of mixed forests on pathogens has been less extensively studied, but several papers report cases of associational resistance (Hantsch et al, 2014;Pautasso, Holdenrieder, & Stenlid, 2005). However, previous studies showed mixed forests do not always show associational resistance to pests and pathogens (Kambach, Kühn, Castagneyrol, & Bruelheide, 2016;Schuldt et al, 2010), suggesting that associational effects may be context dependent, for instance, on abiotic conditions (Jactel, Poeydebat, van Halder, & Castagneyrol, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the number of trees not attacked by pests increases by the most effective dilution and by the physical and chemical masking done by non-host species (Table 1). The increase in all trophic levels makes the community more resistant to biotic and abiotic disorders (DASSOU & TIXIER, 2016;FIELD et al, 2020;GUO et al, 2019;GUYOT et al, 2015;JACTEL et al, 2019;KLAPWIJK et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are also of great ecological relevance because they demonstrate that it is possible to diversify pine monocultures with addition of birch at an early age and then benefit from ecosystem services such as pest protection (Damien et al, 2016;Jactel et al, 2019) and increased diversity of predatory insects (Jouveau et al, 2020) without compromising the wood production of the target species (here maritime pine). Long-term simulations of pine and birch growth on the study sites supported our results (Morin et al, 2020) showing that the ecosystem services associated with pine monoculture diversification can persist as the stand ages.…”
Section: § Transgressive Mixture Effect Was Not Significantly Differe...mentioning
confidence: 86%